Poczucie koherencji w konstruowaniu kariery (kontekst całożyciowego rozwoju jednostki) - Piorunek, Magdalena (Wydawnictwo Naukowe UAM, 2016)
The text The Sense of Coherence in Career Structuring (a Context of Lifelong Development of an Individual) describes the salutogenetic concepts of health and sense of coherence by A. Antonovsky that serve as an inspiration for reflections about the structuring of an individual’s vocational career. The Sense of Coherence (SOC) is a global orientation that expresses the extent to which one has an enduring and dynamic feeling of confidence that: – stimuli coming throughout one’s lifetime from the internal and external environments are structured, predictable and explainable (the sense of comprehensibility – a cognitive component); – resources are at one’s disposal which are adequate to meet the demands posed by these stimuli (the sense of manageability – a cognitive-instrumental component); – these demands are challenges that are worth investing effort and engagement (the sense of meaningfulness – an emotional-motivational component); The essay presents a hypothesis that the Sense of Coher-ence, as it develops over one’s lifetime, may foster an effective structuring (planning and realisation) of one's vocational career. A bi-directional relation exists between the structuring of one’s high and stable sense of coherence and the development of the biographical thinking and shaping of one’s biographical competence. These competencies can be developed in the process of upbringing and education and fostered by vocational guidance, especially in its non-directive dimension (coaching, tutoring).
The Sense of Coherence in Career Structuring (a Context of Lifelong Development of an Individual)
Keywords: sense of coherence; sense of comprehensibility; sense of manageability and meaningfulness; vocational career; biographical thinking; biographical competence; career guidance